EFFECTS OF NICOTINE ON AN IN VITRO RECONSTITUTED MODEL ORAL MUCOSA IN TERMS OF CYTOKINE PRODUCTION - Sheikh, Muhammad Nauman; Hanif, Sajid; Zia, Majid; Qayyum, Zahur (Journal of Ayub Medical College Abbottabad, 2011)
Background: The extensive use of tobacco and its associated problematic health issues have been a concern to mankind. The World Health Organization (WHO) estimates that approximately one-third of the global population aged 15 years or older are smokers and each smoker consumes an average of 15 cigarettes daily. The objective of this study was to establish the effect of nicotine on an in vitro reconstituted oral mucosa model, the effect of treatment with this compound was measured in terms of cytokine production. Method: Observational laboratory based study design was used to carry out the experiment. The reconstituted human epithelium model used in the study was prepared and supplied by Skin Ethic Laboratories, Nice, France. The effect of nicotine on epithelial cytokine production was assessed using commercially available assay kits (R&D systems). This was done using the enzyme linked immuno-sorbent assay. Result: In this study there was evidence that after 5 minutes treatment on un-inflamed mucosa with nicotine at 10 mm concentration GM-CSF release decreased, and also after 24 hours treatment with nicotine at 10mM concentration GM-CSF release increased. TNF-Î± increased release of pro-inflammatory cytokines, IL-6, IL-8, and also GM-CSF from the model mucosa after 24 hours, but had no effect on the release of IL-1Î±., IL-6, IL-8, and GM-CSF after 5 minutes and 24 hours respectively. Conclusion: In conclusion at all the concentrations used in this experiment, nicotine had no effect on the TNF-Î± stimulated tissue and un-inflamed mucosa and had no significant effect on cytokine release including IL-1Î±., IL-6, IL-8, and GM-CSF after 5 minutes and 24 hours respectively. Keywords: Nicotine, oral mucosa, cytokine